2006
DOI: 10.1196/annals.1354.018
|View full text |Cite
|
Sign up to set email alerts
|

Naïve T Cells in the Elderly

Abstract: One of the most striking changes in the primary lymphoid organs during human aging is the progressive involution of the thymus. As a consequence, the rate of naïve T cell output dramatically declines with age and the peripheral T cell pool shrinks. These changes lead to increased incidence of severe infections and decreased protective effect of vaccinations in the elderly. Little is, however, known of the composition and function of the residual naïve T cell repertoire in elderly persons. To evaluate the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 13 publications
3
59
1
2
Order By: Relevance
“…However naïve T cells also enter a state of senescence due to their extended replicative history so as to maintain the homeostasis of the naïve compartment during ageing (Nikolich-Zugich, 2005;Goronzy et al, 2007). Moreover, there are numerous studies that have shown that telomere shortening occurs in both naïve (Pfister et al, 2006) and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However naïve T cells also enter a state of senescence due to their extended replicative history so as to maintain the homeostasis of the naïve compartment during ageing (Nikolich-Zugich, 2005;Goronzy et al, 2007). Moreover, there are numerous studies that have shown that telomere shortening occurs in both naïve (Pfister et al, 2006) and…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both CD4 and CD8 cell populations change during ageing. The major characteristic of this immune ageing process is the decrease in the number of naïve T cells with age (Goronzy et al, 2007;Pfister et al, 2006;Kovaiou et al, 2005). The repeated stimulation of memory cells leads to their replicative exhaustion and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Whit these changes in CD8 + T cell functionality, aged people are more vulnerable to viral infections (Webster, 2000). Naïve CD4 + T cell function in the aged decreases due to the accumulation of intrinsic and extrinsic defects, effectively limiting effective antibody responses (Pfister et al, 2006). The TCR signalling cascade shows age-related modifications as in the case of JAK/STAT pathway (Fulop et al, 2006) and the lipid raft polarization that affects IL-2 and IL-6 receptor signalling in T cells.…”
Section: Naïve and Memory T Cells In Agingmentioning
confidence: 99%
“…T cells, no significant differences in the distribution of lymphocyte subpopulations (CD4, CD45RO, CD8, CD19) were detected between the tumor patients and the healthy controls before and after vaccination. Also the percentage of CD4 T cells expressing CD62L, a homing receptor on naïve T cells, did not significantly differ between the two groups and declined after vaccination, most probably as a result of immune responsiveness to the vaccine antigens, as also described for other vaccines in healthy adults [13,29].…”
Section: Discussionmentioning
confidence: 56%